Washing water pressure and temperature on microbial population of cattle carcasses surface - Saba, Rachel Zoccal [UNESP]; B̈rger, Karina Paes [UNESP]; Rossi, Oswaldo Durival [UNESP] (FapUNIFESP (SciELO), 2010)
The aim of this study was to evaluate the influence of washing water temperature and pressure on mesophilic and psychrotrophic aerobic bacterial populations, yeasts and molds, total coliforms and fecal coliforms population, whereas the cattle carcass surface may become contaminated during the different slaughter procedures and the final carcass washing may reduce microbial population. Samples were taken by sponge swabbing in four areas of carcass surface (flank, neck, chest and rump), from which 20 were washed with water at 25°C and without artificial pressure, 20 with water under a pressure of 3atm, 20 with water at 40°C and without artificial pressure and 20 with water at 40°C under a pressure of 3atm. For control purpose and using the same method to collect more 20 carcasses samples were taken without washing, totaling 100 samples. The results showed that the water at 25°C under 3atm pressure was more efficient to remove microorganisms from carcass surface than the heated water, although this latter promotes a more visible clean carcasses.
Pressão e temperatura da água de lavagem na população microbiana da superfície de carcaças bovinas
Keywords: Carcass decontamination; Cattle carcass; Cattle carcass washing; Cattle slaughter; Fecal coliforms; Food safety